Optical, structural, morphological and chemical properties of doped TiO2 nanoparticles with FeCl3 - Afonso, Cátia (2022)
To achieve high photocatalytic activity, TiO2 nanoparticlesrequire an excitation source in ultraviolet radiation. Incorporating chemical elements into the TiO2 lattice can tune its band gap, resulting in an edge-shifted red absorption to reduce energies, improving photocatalytic performance in the visible region of the electromagnetic spectrum. In this research, TiO2 semiconductor nanoparticles were subjected to a doping process using iron chloride (FeCl3) powder to activate photocatalysis under visible light and consequently improve pollutant capture. To study the effectiveness of the doping process, the main ratios (1:1), (1:1.622) and (1:3) of TiO2:FeCl3 were evaluated using Diffuse Reflectance Spectroscopy (DRS), X-ray diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The main results of this research show that doping TiO2 with FeCl3 shifted the absorption edge to longer wavelength values, changing the optical properties of the material and decreasing the band gap (Eg) of TiO2 compared to the undoped TiO2 (reference). There are no relevant differences between the XRD pattern of the samples with TiO2-FeCl3 and TiO2 nanoparticles (reference). The fraction of the anatase phase in doped TiO2 nanoparticles has the same magnitude as the reference TiO2. Regarding FTIR, the Fe-doping process alters the TiO2 reference spectrum, increasing the intensity of hydroxyl bonds and peaks particularly, indicating the Ti-O-Fe bond vibration.